A high proportion of beta-tocopherol in vitamin E is associated with poor seed longevity in rice produced under temperate conditions - Lee, Jae-Sung; Kwak, Jieun; Cho, Jun-Hyeon; Chebotarov, Dmytro; Yoon, Mi-Ra; Lee, Jeom-Sig; Hamilton, Ruaraidh Sackville; Hay, Fiona R. (Cambridge University Press, 2019)
Seeds of 15 diverse rice accessions, representing aus, indica, temperate japonica and tropical japonica subpopulations, were produced under temperate climate conditions in Korea and used for vitamin E analysis and seed storage experiments at 45°C and 10.9% seed moisture content. High γ-tocotrienol was significantly positively correlated with seed longevity. In addition, a high β-tocopherol proportion relative to δ-tocopherol was significantly negatively correlated with seed longevity. Using high-density single-nucleotide polymorphism marker data, DNA haplotype analysis showed clear allelic variations in the region of two S-adenosylmethionine synthetase genes: LOC_Os04g42095 and LOC_Os11g15410, which regulate the conversion of δ-tocopherol into β-tocopherol. Four indica accessions with rare and subpopulation-specific alleles showed a 2.3-fold lower β-/δ-tocopherol ratio compared with accessions from other subpopulations.